Connecting the mechanisms of T-cell regulation: dendritic cells as the missing link. - Cobbold, S; Adams, E; Nolan, K; Regateiro, F; Waldmann, H (2010)
A variety of different molecular mechanisms have been proposed to explain the suppressive action of regulatory T cells, including the production of anti-inflammatory cytokines, negative costimulatory ligands, indoleamine 2,3-dioxygenase-mediated tryptophan catabolism, CD73-mediated adenosine generation, and downregulation of antigen-presenting cells. Until now it has been unclear how important each of these different mechanisms might be and how they are coordinated. In this review, we examine the hypothesis that it is the interaction between regulatory T cells and dendritic cells that creates a local microenvironment depleted of essential amino acids and rich in adenosine that leads to the amplification of a range of different tolerogenic signals. These signals are all eventually integrated by mammalian target of rapamycin inhibition, which enables the induction of new forkhead box protein 3-expressing Tregs. If correct, this provides a molecular explanation for the in vivo phenomena of linked suppression and infectious tolerance.